Surah Al-Maun And Relationship With Empowerment Of Property - Rajab Al Fathin Muhammad Nasution; Muhammad Rifki Hanan; Muhammad Iqbal Nabawi; Hafiz Hamdi Nasution; Agusman Damanik (Jurnal Multidisiplin Sahombu, 2025)
The purpose of this study was to analyze al-Ma'un's from a neuroscience perspective that occurred at the Muhammadiyah Wates Orphanage . The research approach used is descriptive qualitative and field research , with library research method . This research discusses Al- Ma'un Theology which is one of the Muhammadiyah movement taught by KH. Ahmad Dahlan who is translated into three pillars , namely education ( Schooling ), health ( healing ), and social services ( feeding ). From there , we need the concept of mind or qalb , and spirit in realization the theology of al-Ma'un . Because in neuroscience the metaphysical concept of the brain will optimize various human potentials . Neuroscience also examine the brain's awareness and sensitivity in terms of biology , perception , memory , and its relationship to learning . Religious learning that is carried out repeatedly at the Muhammadiyah Orphanage LKSA makes the brain work easier , this happens because the brain already knows from which basket the data related to the lesson must be taken so that it can understand completely​ knowledge even up to saturation point .